Terminologization of adjectives in the texts of scientific communication (on the material of the sublanguages of Electrical Engineering) - Шапа, Людмила Николаевна; Томасевич, Надежда Петровна; Данцевич, Людмила Георгиевна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”)
The paper describes the peculiarities of terminologization of adjectives functioning in the texts of scientific communication. The adjectives-terms were analyzed in the three aspects: lexical, grammatical and semantic. Using the commonly accepted classification system of term meaning type identification the authors made an attempt to apply it to the terminologized adjectives. The results of the research have shown that in some cases an adjective when turning into the term loses its semantic dependence on noun.